STRATEGIC MANAGEMENT OF AI ART EXHIBITIONS - J. Refonaa; Upadhyay, Satish; Singh, Tanya; Sharma, Divya; Dhawas, Nitin Ajabrao; Aggarwal, Prateek; Datar, Dinesh Shravan (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The art of AI exhibitions management is an emerging area of frontier by the array of technology, imagination, and culture administration. The emergence of artificial intelligence as a driver in the production of art has introduced new issues and opportunities to curators and managers regarding how to conceptualize, organize and maintain exhibitions dealing with the issue of algorithmic creativity. This study indicates that AI art exhibitions should be managed in a comprehensive manner that addresses the strategic management of art exhibitions, their curation, operations, and the audience. It begins by defining the scope of AI art and contextualising it within the context of bigger conversations on digital culture and innovation management. The framework focuses on creating effective visions, missions, and goals that outline the value and the meaning of AI-based experiences of art. Through market and audience analysis, institutions will be in a better position to have a clear vision of the new demands and position themselves in the competitive arena of the cultural sector. The essence of successful exhibition curation consists in the developed concept of AI-based works selection principles including ethical considerations, aesthetic characteristics, collaboration trends that can unite artists, technologists, and curators. The operational strategies prove the need of the good technological foundation, the effective resource allocation, and the active risk management, particularly taking into account the fact that AI systems can be described as dynamic and experimental. The marketing strategies such as the narrative based branding and the cooperation with the digital media and the immersion of the audiences also precondition the rise of the degree of the public interest.